COMPARATIVE DESCRIPTION OF THE WORD FORMATION OF MEDICAL TERMS - Xalmuratov, Tajetdin Jumashevich; Turganbaeva, Abadan Sarsenbaevna (SCIENCE and SOCIETY, 2026)
The article examines the word-formation features of medical terms in the Russian and Karakalpak languages. Common and specific term-formation patterns are identified. The study shows that affixation and compounding prevail in Russian, while borrowing, calquing, and grammatical adaptation are significant in Karakalpak. The findings may be applied in terminology, linguistics, and translation practice.